Visões do rosto e sua importância na construção de personagens no cinema - Soares, Lidiane (My University, 2023)
This study aims to understand the portrayal of the face in cinema as an important resource for character building and characterization in the cinematographic language. The material here presented is organized into three main chapters that bring relevant discussions about cinema, character, face, and cinematographic language. The methodology is based on a qualitative approach, initially carrying out bibliographical research, which addresses important authors discussing cinema nowadays. In the end, the case study is pointed out, with an in-depth look at the actress Tilda Swinton and three prominent characters in her career, analyzing her face in cinematographic productions. They are: "Orlando" (1992), "The Chronicles of Narnia: The Lion, the Witch and the Wardrobe" (2005), and "We need to talk about Kevin" (2011). This scenario helps in understanding the importance of the actor's face for character building in cinema, especially from the point of view of cinematographic language. It is a fundamental and representative point in cinema narrative. Its development demands adequacy, elaboration and creativity from the different professionals participating in the creation of the audiovisual work at stake, with the appropriate exploration of resources involving skill and technique in the use of cinematographic language. [resumo fornecido pelo autor]
O presente estudo tem como objetivo principal compreender o rosto no cinema como recurso importante para a construção e caracterização de personagens a partir da linguagem cinematográfica. A abordagem em questão está organizada em três capítulos principais, que trazem discussões relevantes sobre cinema, personagem, rosto e linguagem cinematográfica. A metodologia possui viés qualitativo, sendo inicialmente realizada uma pesquisa bibliográfica, que aborda autores importantes em discussões sobre cinema, na atualidade. Ao final destaca-se o estudo de caso, lançando-se um olhar aprofundado sobre a atriz Tilda Swinton e três personagens de destaque em sua carreira, com a análise de seu rosto em obras audiovisuais. São elas: Orlando (1992), As Crônicas de Nárnia: o Leão, a Feiticeira e o Guarda-Roupa (2005) e Precisamos Falar sobre o Kevin (2011). Esse cenário permite compreender a importância do rosto do ator para a construção de personagens no cinema, especialmente sob a ótica da linguagem cinematográfica. Ele apresenta-se ponto fundamental e representativo da narrativa cinematográfica. Necessita ser trabalhado de forma adequada, elaborada e criativa por diferentes profissionais na criação da obra audiovisual que está em jogo, com a exploração adequada de recursos que envolvem habilidade e técnica no uso da linguagem cinematográfica. [resumo fornecido pelo autor]
Keywords: Publicidade; Cinema; Personagens cinematográficos; Visagismo